Hak Anak terhadap Nafkah dalam Perundangan Islam: Sejauh Manakah Bapa Bertanggungjawab Menanggung Nafkah Anaknya (Kanun: Jurnal Undang-undang Malaysia, 2013)
The legal relationship between parents and children creates various rights and responsibilities. These rights are inclusive of rights in relation to person and property of the children. Those rights are for example, rights to parenting, breastfeeding, protection and guardianship, custody, maintenance and inheritance. This article will examine issues relating to children's rights to maintenance in general under Islamic law and situations that make them qualified to maintenance. Examination extends to provision of Islamic law that is applicable in Malaysia and its application in Islamic Family Law (Act). This paper will further examine the extent of the father's responsibility in providing maintenance to his children in line with the will of the Shari'ah and present demand; and in what situations this responsibility transfers to the next of kin.Keywords: maintenance, children's rights, Islamic law, Malaysian law